Japanese naval vessels at the end of World War II - Fukui, Shizuo (White Lotus, 2009)
This is a very simple form of a record of all combatant vessels and the representative minor miscellaneous vessels, inclusive of special attack crafts of the ex-Imperial Japanese Navy at the end of the war. Some army crafts which had more or less combatant value have also been included. The aim of this book has been to keep as clear of technicalities as possible in order that it may be extensively and easily understood by the authorities of the allied navies engaging in the disposition of the ex-Japanese naval vessels.